De la enseñanza superior en España. La enseñanza del latín en España - Unamuno, Miguel de (Historia de las Universidades, 2022)
If the reform of secondary education enacted in 1894 by the minister Segismundo Moret encouraged Miguel de Unamuno to print some reflections on the teaching of Latin in Spain, the disaster of 98 prompted him to write about higher education. In both cases, the underlying idea was to "make a homeland", to link the task of teaching with the truth, in the face of a sad realisation: "The school of lies is what is commonly called patriotism". Unamuno does not believe in official reforms, but in people, which is why he criticises, in a phrase that has become famous, "this weaving and unweaving of Penelope's web of our official teaching from the ministry".